KEWENANGAN PEMERINTAH KOTA DALAM PELAKSANAAN UJI EMISI KENDARAAN UMUM DI KOTA PEKANBARU TAHUN 2017-2019 - Reza Juli Yandra; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Transportation is the process of moving goods and people from the place of origin to the place of destination. Transportation is basically one of the most important components as a supporter, driver and driver for the growth of a region. In the field of road traffic and transportation, prevention and control of the environment must be carried out, namely in Law Number 22 of 2009 concerning Road Traffic and Transportation. The problem in this study is that the City Government's authority is not maximally implemented, resulting in a decrease in the number of public vehicles in conducting emission tests. The purpose of this study is to describe how the authorities and constraints faced by the city government in implementing the emission test of public vehicles in the city of Pekanbaru.The research approach used is qualitative with descriptive analysis method by describing phenomena and data accurately. The research location is in UPTD. Motor Vehicle Testing of the Department of Transportation, Communication and Information of Pekanbaru City. The types and sources of research data are divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to exhaust gas emission testing of public vehicles. Data collection techniques used by interview and documentation.The results of this study are that first, the authority given to the city government based on Law No. 22 of 2009 as the basis for the rules that regulate it is considered not yet implemented or implemented optimally even though public vehicles that are operated on the road are required to carry out periodic tests as one of the emission tests. as a condition of roadworthiness. Public vehicles that do not carry out emission tests can result in air pollution and global warming. the authority of the City Government obtained when viewed from where the authority was obtained according to H.D. Van Wijk / Willem Konijnenbelt, it can be seen in 3 sources of authority, namely attribution, delegation and mandate. Second, the City Government Constraints in the implementation of emission tests on public vehicles that keep repeating themselves at the UPTD. Motor Vehicle Testing in Pekanbaru City, namely the constraints of facilities and infrastructure that are not optimal and the constraints of human resources which are still minimal in quantity and quality.Keywords: Authority, City Government, Emission Test